APPLICATION OF SOFT RELINING MATERIALS BY DENTISTS - A PILOT STUDY - Ilian Hristov; Diyan Slavchev; Dobromira Shopova; Lyubomir Grozev; Bozhana Chuchulska (Peytchinski Publishing, 2017)
Purpose: The aim of this study is to analyse the dentists, awareness of the soft relining materials - their behaviour, advantages and disadvantages. Materials and methods: A direct survey method was applied, as well as a documentary method of gathering statistical information. For the purpose of this investigation, a standard questionnaire has been presented, consisting of seven questions each. Results: The age group have no influence on the frequency of use of soft relining materials in practice. According to 49.57% of the interviewed dentists, the most frequently observed disadvantage is the hardening of these materials in a very short notice. Staining from food and beverage and frequently noticed bond failure from the denture basis were also observed, 18,26% consider discolouration from disinfectants a problem as well. The majority of the interviewed (56,52%) have been answered, that their patients are pleased from the applied SRM. 70,43% have been answered that SRM matches the denture basis and the rest 29,57% have been pointed out that these materials are not very aesthetic. Discussion: Although the majority of the dentists declare, that they are aware of the properties of the soft relining materials, they are a little bit sceptical about their use in practice. On the other hand, the patients are satisfied and find them very useful and beneficial. Conclusion: It can be concluded, that he majority of the dentists are very well acquainted with the soft relining materials, their purpose and way of application.